The alcohol industry's involvement with road safety NGOs - Ivy Stein; Abdulgafoor M. Bachani; Connie Hoe (BMC, 2022)
Abstract Background Road crashes are a major cause of death among all age groups and the leading cause of death among persons 5-29 years, according to the World Health Organization. One key risk factor is drink-driving. While the world's leading beer, wine, and spirit producers have pledged to combat drink-driving, there is increasing evidence showing the alcohol industry's promotion of solutions which minimally impact sales. One strategy is forming partnerships with road safety non-governmental organizations (NGOs). Given this, the primary objective of this study is to understand the extent to which the alcohol industry is involved with road safety NGOs around the world. Methods A desk review from July 2020 to March 2021 was conducted to assess the alcohol industry's involvement with various road safety NGOs (n = 256) in 92 countries. Financial documents press releases, annual reports, social media platforms, and other resources were analyzed to uncover relationships between the alcohol industry and NGOs. Results Out of 256 NGOs, n = 11 (4%) showed direct ties to the alcohol industry, and n = 3 (1%) showed indirect ties. NGOs involved with the alcohol industry were found in five continents and n = 8 of the 11 NGOs (73%) partnered with transnational alcohol manufacturers. Interventions supported by these partnerships were primarily mass media campaigns, free-ride and ride-sharing campaigns, and drink-driving educational events where alcoholic or zero-percent alcoholic beverages were sold or provided. These interventions are largely inconsistent with evidence-based best practice recommendations. Relationships between the alcohol industry and road safety NGOs lacked public transparency on key details such as terms of partnerships and funding amount and terms. Conclusions The study showed a clear effort on behalf of the alcohol industry to partner with road safety NGOs around the world. Findings underscore the need for the road safety community to generate consensus on involvement of the alcohol industry and suggest the need for more transparency on details of partnerships involving road safety. Findings also highlight the importance of local and national government support of road safety initiatives and road safety NGOs to avoid dependence on controversial funding from the alcohol industry.